Peri-ictal headache due to epileptiform activity in a disconnected hemisphere - Vydrova, Rosa; Kršek, Pavel; Kyncl, Martin; Jahodova, Alena; Dvorak, Josef; Komarek, Vladimir; Delalande, Olivier; Tichy, Michal (Epileptic disorders, 2014)
A 4-year-old girl with intractable epilepsy due to left-side hemispheric cortical dysplasia underwent a hemispherotomy. She was seizure-free after the surgery. EEG showed persistent abundant epileptiform activity over the left (disconnected) hemisphere, including ictal patterns that neither generalised nor had clinical correlates. Antiepileptic medication was completely withdrawn four years following the surgery. One week after the withdrawal, she developed episodes of intense left-sided hemicranias (ipsilateral to the surgery) with vomiting and photophobia that did not resemble her habitual seizures and were unresponsive to non-steroidal anti-inflammatory drugs. Video-EEG showed association of the headache attacks with ictal patterns over the disconnected hemisphere. Brain MRI revealed increased signal changes in the left hemisphere. Attacks responded promptly to i.v. midazolam and carbamazepine at a low dose. Mechanisms underlying peri-ictal headache originating in the disconnected hemisphere are discussed. [Published with video sequences].
Keywords: Midazolam; mozek; předškolní dítě; Humans; Brain; Headache; Functional Laterality; hemisferektomie; Hemispherectomy; peri-ictal headache; AED withdrawal; elektroencefalografie; bolesti hlavy; midazolam; antikonvulziva; funkční lateralita; Child, Preschool; neurochirurgické výkony; záchvaty; Epilepsy; Anticonvulsants; Electroencephalography; Seizures; ženské pohlaví; Neurosurgical Procedures; epilepsie; lidé; karbamazepin; hemispherotomy; Carbamazepine; Female